Portrait of Public Debt, Fiscal Space, and Debt Impact: Islamic Finance Study on Islamic Countries Territory - Zidny Nafi' Hasbi (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2022)
Policymakers, the Public debt is a problem that the monetary and fiscal authorities have long been concerned about. The amount of public debt concerning fiscal viability and the financial crisis has received a lot of attention recently. This study's goal is to examine and evaluate how the function and impact of debt, both external and internal, on the macroeconomic situation of various countries. The researcher will present several cases of empirical evidence regarding the impact of debt on the socio-economics of a country. The main focus of this research discussion is on the theoretical study of debt and the impact of debt in various countries in the region, as well as the views of Islamic thinkers on public debt. A library study was the research methodology employed. by collecting, identifying, and analyzing articles and related references (literature review) related to the focus research. Furthermore, researchers will examine several cases of portraits of various empirical evidence concerning the country's socioeconomic debt. The findings demonstrate that an Islamic state will be successful based on its ability to collect taxes, alms, and other required and optional sources of income, as well as revenue from public works projects, real estate, and natural resources. To achieve a balanced budget and prevent wasteful spending, the state will implement the middle-at-tawasuth principle.